TAXPAYER COMPLIANCE BEHAVIOR ON MUSLIM MICRO, SMALL, AND MEDIUM ENTERPRISE ACTORS IN PASURUAN CITY INDONESIA - Mahfudz Sayudi; Parmujianto Parmujianto (Akademika : Jurnal Pemikiran Islam, 2023)
The rapid growth of the Micro, Small, and Medium Enterprise (MSME) sector in Pasuruan City does not align with the anticipated level of taxpayer compliance behavior. This discrepancy creates a conflicting situation where the potential revenue generated by the sector clashes with the issue of tax non-compliance, posing a threat to Regional Revenue and the Islamic economy. Therefore, this study examined the understanding, behavior, and Maqasid Al-Shari'ah review of taxpayer compliance behavior of Muslim MSME actors in Pasuruan using a phenomenological qualitative approach. Data were collected through open observation techniques, in-depth interviews, and documentation. The results showed that applicable tax policy was understood through socialization organized by the Cooperative and MSME Office continuously with a humanist approach. Meanwhile, the relationship between Maqāṣid al-Sharī`ah values and tax policy was to provide education by conducting socialization to the community regarding its content and benefits. In the concept of Maqāṣid al-Sharī`ah adh-ḍarūriyāt, the tax policy carried out by the government was included in Hifdzul Maal. This was the top Maqāṣid al-Sharī`ah benefit as a reinforcement of religiosity theory by adding the factors of blessing and economic justice. In contrast, the tax function, policy, registration, payment, rates, and reporting were reinforced by Muslim religiosity.